Pleurotus ostreatus is a potential biological control agent of root-knot nematodes in eggplant (Solanum melongena) - Nyangwire, Betty; Ocimati, Walter; Tazuba, Anthony Fredrick; Blomme, Guy; Alumai, Alfred; Onyilo, Francis (Frontiers Media, 2024)
Introduction: The management of root-knot nematodes has predominantly been based on use of chemicals, which are detrimental to the environment and human health. Biological control provides alternative management. This study evaluated the potential of using Pleurotus ostreatus, an edible mushroom species to control Meloidogyne spp. in eggplants.